3 weeks in the rainforest : a rapid inventory in the Amazon - Swanson, Jennifer (Charlesbridge, 2025)
"A team of scientists from the Field Museum works with local communities and the Colombian government to conduct a cooperative survey of the Amazon rainforest. After three weeks in the field, the team shares its findings and makes recommendations for protecting the region's biological and cultural diversity"--